Novel Piperidine and 3,4-dihydro-2H-pyrrole Alkaloids from Tilia platyphyllos and Tilia cordata Flowers - Symma, Nico; Bütergerds, Marek; Sendker, Jandirk; Petereit, Frank; Hake, Alexander; Düfer, Martina; Hensel, Andreas (Planta Medica, 2021)
Lime flowers, traditionally used for medical purposes for the treatment of symptoms of the common cold and mental stress, consist of the dried inflorescences including the floral bracts of Tilia cordata, Tilia platyphyllos, Tilia × vulgaris, or mixtures thereof. During phytochemical investigations, 6 different alkaloids – not described until now – were detected in T. cordata and T. platyphyllos flowers. They have been isolated and characterized as alkaloids with a dihydro-pyrrole and a piperidine substructure, respectively. Compounds 1a and 1b (tiliines A and B) are characterized as 2 diastereomers containing a 2-methyl-3,4-dihydro-2H-pyrrol-3-ol, connected via a C-10 alkyl chain to a O-glucosylated hydroquinone moiety. Compounds 2a and 2b (tiliamines A and B) are diastereomers of a 2-methyl-substituted piperidin-3-ol, coupled via a C-9 alkyl chain again to an O-glucosylated hydroquinone moiety. Compounds 3a and 3b (tilacetines A and B) are 3-O-acetylated derivatives of tiliamines. Quantification of the 6 alkaloids by HPLC-ESI-qTOF analysis indicated the presence of all alkaloids in T. cordata flowers and T. platyphyllos flowers, bracts, and leaves, with tiliines A and B and tilacetines A and B being the major compounds. Acetone/water turned out be the best extraction solvent for the alkaloids, but ethanol and ethanol/water mixtures also can be used for effective extraction. Furthermore, the alkaloids are found in hot water extracts, which are typically used in the traditional medicine.
Keywords: Tilia platyphyllos; Tilia cordata; Malvaceae; Tiliae flos; alkaloid; dihydropyrrole; piperidine